Study on Strength Characteristics of Pervious Concrete Using Mineral Admixtures - Avinash, Lakshmireddygari; Adarsh Reddy, Pothireddy; S.Vivek, S (International Journal of Engineering and Technology, 2018)
Pervious concrete is a special type of concrete emerged out in the concrete world. It is referred as porous concrete or no fines concrete. The porous concrete has wide applications in the pavement with low traffic intensity, sidewalks, pathways, platforms, parking lots etc. Since the pervious concrete allows the groundwater replenishment and prevents the pool of water standing on the earth surface during rainfall-runoff, it helps in the stormwater management. In the present work, the partial replacement of cement with silica fume (SF) and metakaolin (MK) as mineral admixtures to an extent from 10 to 30 % by varying water-cement (w/c) ratio from 0.36 to 0.40 was done to study the effect on the performance of pervious concrete. From the results, an optimum w/c ratio was found to be as 0.38 along with 1.5% of the superplasticizer. The experimental results reveal that the compressive strength of pervious concrete containing mineral admixtures was found to be better than the compressive strength of conventional pervious concrete. Among three different percentage of substitutes used, 20% was found to be an optimum value in both the cases. Pervious concrete with SF as admixture exhibited better strength among the two admixtures..